Impact of landfill leachate on the germination of Cucumber (Cucumis sativus) - Franco, Heider Alves; Silva, Maria Eduarda Rocha Valente da; Silveira, Millena Ferreira da; Marques, Monica Regina da Costa; Thode Filho, Sérgio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The generation of landfill leachate occurs due to the degradation of solid waste by the presence of microorganisms. The bioassays allow to understand the relationship between the medium and the leachate, determining the lethal concentration capable of inhibiting 50% of test organisms (LC50), the lowest concentration with observed deleterious effect (LOEC), and the highest concentration without observed deleterious effect (NOEC). This work aimed to determine the impact of landfill leachate on germination and development of radicle and aerial part of cucumber (Cucumis sativus) on two substrates. The design was completely randomized and 6 treatments with increasing doses (leachate + deionized water): T1 = 3.125% + 96.875%; T2 = 6.25% + 93.75%; T3 = 12.5% + 87.5%; T4 = 25% + 75%; T5 = 50% + 50% and T6 = 100% leached, and the control (TC) with 100% deionized water, both in triplicates for filter and soil paper substrates. Cucumber tolerance to leachate was identified. It was not possible to determine the LC50 from the treatments, however the 50% and 100% doses inhibited the germination by 83% and 100%, and the NOEC and LOEC values were identified in treatments 12.5%/25% and 25%/50% on filter paper and soil, respectively.